A12 Loss of proteostasis in huntington disease – lessons from cockayne syndrome. (12th September 2022) - Wagner, Maximilian; Khalid, Fatima; Zhu, Gaojie; Lindenberg, Katrin; Landwehrmeyer, G Bernhard; Mulaw, Medhani; Iben, Sebastian
Abstract : Huntington disease (HD) is an inherited neurodegenerative disease. The stability of the proteome – proteostasis – is crucial for cellular integrity. Proteins are synthesized by ribosomes consisting of ribosomal proteins and catalytic active ribosomal-RNA (rRNA). rRNA is encoded by the rDNA and transcribed by the RNA-polymerase I transcription machinery (Pol-I). The progeria Cockayne syndrome (CS) is caused by mutations in transcription factors of Pol-I. A malfunction of ribosomes in CS leads to an increase in translational errors and a loss of proteostasis. Extracted gene-expression patterns of CS display a strong enrichment of genes typical for HD and can distinguish Huntington disease patient probes from age and sex matched unaffected controls. Furthermore, HTT is known to localize to the nucleolus, the locus of rDNA transcription. ChIP analysis revealed an association of HTT to the rDNA, suggesting a role of HTT in rDNA transcription. We also detected alterations in rRNA maturation in HD patient samples. Moreover, the accuracy of protein synthesis at the ribosomes is affected, translational fidelity assays showed an increase in translational errors in a polyQ-length dependent manner. The proteome of severely affected R6/2 mouse (8 weeks old) brains showed reduced stress-resistance and temperature-induced aggregation. The proteome of the only mildly affected HdhQ111 mice (12 months old) did not show these changes. Taken together, our findings suggest a tight correlation of proteome instability and neurodegeneration. The increased error rate in the translational process could help to explain the observed loss of proteostasis in Huntington disease.